Affectivity in women victims and non-victims of intimate partner violence attended in a university clinic using the Rorschach psychodiagnosis - De La Cruz Valdiviano, Carlos (2015)
The goal was to compare the characteristics of affection in women victims and non victims of couple violence in a university clinic by Rorschach . It was based on a mixed approach quantitative descriptive comparative and qualitative turn through discourse analysis of the responses given by subjects in the protocols. Affectivity in women victims and non-victims of partner violence was characterized , to that end the Rorschach and Self-Diagnosis Questionnaire violence by intimate partners , who collected data on participants and information on dating violence was applied suffered . A quantitatively significant differences (p < 0.05) between female victims and non-victims of violence in some Rorschach variables that make up the cluster indicators affectivity control and modulation of emotions (FC), emotional responsivity (Afr) were revealed, search of independence and assertiveness (S) and activity level of analysis and synthesis (complex responses) representing some features of emotion more inadequate female victims compared to women not victims of partner violence . Furthermore, qualitative differences in affectivity of Rorschach Content, analyzed from the perspective of the Comprehensive System among female victims and non-victims of violence being predominantly aggression, repressed fantasies of death in the first were found.